2020
DOI: 10.1080/23723556.2020.1789418
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid reduces the autophagic flux in hypothalamic neurons by impairing autophagosome-lysosome fusion and endolysosomal dynamics

Abstract: High-fat diet (HFD)-induced obesity is associated with increased cancer risk. Long-term feeding with HFD increases the concentration of the saturated fatty acid palmitic acid (PA) in the hypothalamus. We previously showed that, in hypothalamic neuronal cells, exposure to PA inhibits the autophagic flux, which is the whole autophagic process from the synthesis of the autophagosomes, up to their lysosomal fusion and degradation. However, the mechanism by which PA impairs autophagy in hypothalamic neurons remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…More importantly, we hoped to raise questions to help investigate the mechanical requirements of autophagy and appreciate the extent to which mechanical signals affect this process. For instance, a diet rich in saturated fatty acids can negatively impact autophagic flux in neurons (278,279). Interestingly, as the steric conformation of these phospholipids is known to mechanically decrease membrane bending, it could consequently impair autophagy by preventing vesicle fusion.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we hoped to raise questions to help investigate the mechanical requirements of autophagy and appreciate the extent to which mechanical signals affect this process. For instance, a diet rich in saturated fatty acids can negatively impact autophagic flux in neurons (278,279). Interestingly, as the steric conformation of these phospholipids is known to mechanically decrease membrane bending, it could consequently impair autophagy by preventing vesicle fusion.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this question, we treated hypothalamic POMC-like cells with BSA (serum bovine albumin) and 100 µM of PA and SA at different time points (0, 2, 4, and 6 h) and evaluated the total protein levels of the principal CMA players (LAMP2A and HSC70) by Western blot post SatFAs treatment. We chose 100 µM of PA and SA because this is the concentration of PA that has been observed to accumulate in the hypothalamus of mice fed an HFD [30] and because this is the concentration reported to inhibit macroautophagy in POMC-like neurons [22,23]. Compared with BSA, we observed that the total protein levels of LAMP2A, but not HSC70, decreased after 6 h of PA and SA treatment (Figure 1A-C).…”
Section: Total and Lysosomal Lamp2a Protein Levels Decrease In Pomc-l...mentioning
confidence: 96%
“…Previous results have shown that palmitic acid inhibits macroautophagy in hypothalamic POMC-like cells [22,23]. Regarding CMA, a recent work showed a decrease in the LAMP2A staining intensity after palmitate treatment in hypothalamic neurons [27].…”
Section: Total and Lysosomal Lamp2a Protein Levels Decrease In Pomc-l...mentioning
confidence: 96%
See 1 more Smart Citation
“…Then, 4 6-diamidino-2-phenylindole (DAPI; Thermo Fisher Scientific) was used to counterstain the nuclei. To determine autophagy flux, accumulation of GFP-and/or RFP-LC3 signals was visualized by fluorescence microscope and quantified according to previous publication [19].…”
Section: Immunofluorescencementioning
confidence: 99%